THE EFFECT OF ADDITION OF PIRDOT LEAF EXTRACT AND JUICE OF RED WATERMELON ALBEDO ON CARBONATED COCONUT DRINK OF BLOOD GLUCOSE LEVELS OF MICE - Utami Barus, Cindy Puteri (Journal of Food and Pharmaceutical Sciences, 2019)
In this study, the effect of addition of pirdot leaf extract and juice of red watermelon albedo on carbonated coconut drink of blood glucose levels was done by giving samples orally to mice. This study used 30 white male wistar mice, which were divided into 6 treatment groups that containing 5 mice in each group i.e: normal untreated mice given with aquades (negative control), diabetic untreated mice given with aquades (positive control), normal mice treated with 0.6 mL per 27 g bw per day of carbonated coconut drink, diabetic mice treated with 0.6 ml per 27 g bw per day of carbonated coconut drink, normal mice treated with 0.6 mL per 27 g bw per day of commercial soda, and diabetes mice treated with 0.6 mL per 27 g bw per day of commercial soda. The treatment was carried out for 14 days and observations made on blood glucose levels and body weight of mice. The results showed that giving of carbonated coconut drink by adding pirdot leaf extract and juice of red watermelon albedo had a highly significant effect on blood glucose levels of mice. The effect was hypoglycemic effect, which can reduce blood glucose levels on the diabetes group about 6,536%, while on the non-diabetic group about 3,316%. However, the giving of commercial soda provides a hyperglycemic effect that increased blood glucose levels about 19,787% on the diabetic group, while on the non-diabetic group about 12,750%. In addition, giving of carbonated coconut drink by adding pirdot leaf extract and juice of red watermelon albedo had a highly significant effect on the body weight of mice. The effect was weight gain on the diabetes group about 4,171%, while on non-diabetics about 2,564%. However, giving commercial soda had a weight loss effect about 33,750% on the diabetic group, while on the non-diabetic group about 6,884%.